2019
DOI: 10.1088/1757-899x/688/3/033032
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmone resonance sensor for biomimetic detection of progesterone with macroporous molecularly imprinted polymers prepared by visible light

Abstract: Reversible addition-fragmentation chain transfer (RAFT) polymerization mechanism was used for the preparation of molecularly imprinted polymers (MIPs) film using 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid (CDTPA) as chain transfer reagent and visible light initiator. In addition, the effect of CDTPA concentration on the polymerization rate was monitored, establishing that too high CDTPA concentration would inhibit the polymerization rate. The MIPs film was characterized by contact angle me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…After SAMs formation, a noticeable decrease in CA values was observed. Similar behavior has been reported by other authors (25,26) and can be explained by terminal amino groups in the cysteamine structure attributing greater hydrophilicity to the surface.…”
Section: Resultssupporting
confidence: 90%
“…After SAMs formation, a noticeable decrease in CA values was observed. Similar behavior has been reported by other authors (25,26) and can be explained by terminal amino groups in the cysteamine structure attributing greater hydrophilicity to the surface.…”
Section: Resultssupporting
confidence: 90%
“…However, upon adsorption of the Cys-epitope, the gold surface exhibited a significant change in static angle, becoming highly hydrophilic (8.95°), as shown in Figure B. This increase in hydrophilicity is likely due to the assembly of cysteine’s –SH groups on the gold surface, forming a uniform layer of Au–S bonds . Also, the templated surface showed no fluorescence properties since the peptide lacked a fluorophore moiety.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This increase in hydrophilicity is likely due to the assembly of cysteine’s –SH groups on the gold surface, forming a uniform layer of Au–S bonds. 41 Also, the templated surface showed no fluorescence properties since the peptide lacked a fluorophore moiety. When comparing the contact angles of AP-GQD-AuNP-MIP and AP-GQD-AuNP-NIP films, it was observed that the former (30.1°) exhibited higher hydrophilicity than the latter film (40.4°).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, PG was used as the template molecule to synthesize the magnetic molecularly imprinted microsphere (Fe 3 O 4 @MIM), which was carried out according to the principle of our previous report [31]. During the experiments, 0.1 mmol PG and 0.4 mmol function monomer MA were dissolved in 20 mL acetonitrile, and this solution was put into a tube to be pre-polymerized for 3 h at room temperature.…”
Section: Synthesis Of Fe 3 O 4 @Mimmentioning
confidence: 99%